Medical costs of overweight and obesity in public hospital - Foo, Lee Peng; Hamzah, Hanny Zurina; Mohamed Nor, Norashidah; Said, Rusmawati (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
Obesity and overweight are a highly prevalent problem in the recent years, resulting in a significant financial burden to the healthcare system worldwide. The increased prevalence leads to increased multiple chronic illnesses incidence. This inevitably sparks the substantial surge in medical costs for the treatment of obesity. One-part Generalized Linear Model (GLM) has been applied on the patient-level data obtained from Serdang Hospital. This finding was unexpected and suggests average obesity and overweight patients does not contribute to high personal medical cost due to the heavily subsidized programs and policies by the government, the medical cost for these burgeoning issues is lower compared to normal weight patient. Although the study has failed to highlight the actual cost of obesity and overweight, but it has provided a basic framework for better understanding of their effects, under governmental subsidiary programs.